COVID-19 Pandemic: Economy Transformation in Conditions of Restrictions and Uncertainty - N. V. Barinova (Plekhanov Russian University of Economics, 2021)
COVID-19 pandemic drastically changed life of people all over the world. The economic situation has become unique in new history. When restrictive measures were introduced economy in the majority of countries functioned according to the temporary economic model. The article studies key economic figures characterizing the economic situation during the first wave of the pandemic, as well as changes in customer behavior of people connected with restrictive measures. The author supports the opinion of some researchers that leaders of many states should pay serious attention to the development of economy of disasters, as COVID-19 pandemic is a real disaster. In this connection the most important aspects of state policy should include: provision of the overall country security and safe life in the critical situation, the development of international public health services and information systems based on network on-line platforms, industry 4.0 and artificial intellect. Proposals were put forward aimed at designing the complex concept of economy of disasters, which shall be developed on the basis of advanced achievements in the fields linked with providing safe life of people. According to the author this concept should be ratified by heads of leading states of the world. Conclusions concerning prospects of developing global economy after COVID-19 pandemic were drawn.